2012
DOI: 10.1080/14775085.2012.734060
|View full text |Cite
|
Sign up to set email alerts
|

International tourists' perceptions of crime–risk and their future travel intentions during the 2010 FIFA World Cup™ in South Africa

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 58 publications
3
26
0
Order By: Relevance
“…Negative media coverage of a destination appears to influence risk perceptions and destination choice. George and Swart (2012), in their study of 2010 FIFA World Cup tourists' crime-risk perceptions, found that respondents who originated from Australia and the UK felt safer at night than those from Asia. Reisinger and Mavondo (2006) in their travel-risk study established that US and Australian tourists are more likely to perceive travel as risky compared to British, Greek, and Canadian tourists.…”
Section: Perceived Risk Safety and Tourismmentioning
confidence: 96%
See 3 more Smart Citations
“…Negative media coverage of a destination appears to influence risk perceptions and destination choice. George and Swart (2012), in their study of 2010 FIFA World Cup tourists' crime-risk perceptions, found that respondents who originated from Australia and the UK felt safer at night than those from Asia. Reisinger and Mavondo (2006) in their travel-risk study established that US and Australian tourists are more likely to perceive travel as risky compared to British, Greek, and Canadian tourists.…”
Section: Perceived Risk Safety and Tourismmentioning
confidence: 96%
“…In particular, crime risk has been associated with mega-sporting events (Barker et al, 2003;George & Swart, 2012), and the threat of terrorism has also been a particular concern to Olympic Games' host nations (Gold & Gold, 2010;Neirotti & Hilliard, 2006;Qi et al, 2009;Toohey & Taylor, 2008). Between the period 1972 and 2004, Toohey and Taylor (2008) identified 168 terrorist attacks related to sports.…”
Section: Perceptions Of Crime Risk and Terrorism Risk And Mega-sportmentioning
confidence: 98%
See 2 more Smart Citations
“…Man-made disasters cause permanent and serious damage. George and Swart (2012) further argued that man-made disasters may have even a detrimental effect on tourist benefit perception that will, in turn, impact the destination image [28]. In recent years, when tourists make travel decision with friends or family, there has been increasing concern about man-made disasters when choosing a destination [18].…”
Section: Hypothesis 6 Tourist Benefit Is Positively Related To Destimentioning
confidence: 99%